(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
Shirley P. França works in the field of Performing Arts, Education, Literature and Popular Culture as an actress, educator, puppetter, storyteller and brincante. Matriarch of the family troupe Companhia Carroça de Mamulengos has traveled Brazil for 43 years promoting Art and Culture. This article presents an interview with Schirley P. França, addressing her trajectory and experiences along the journey as an artist and mother, since childhood and the influence of women in the family, going through the theatrical adventures of adolescence, the long years with the Carroça de Mamulengos and the dream of graduating from university, which was achieved in 2020.